Detection and attribution of an anomaly in terrestrial photosynthesis in Europe during the COVID-19 lockdown - Angela Che Ing Tang; Christophe R. Flechard; Nicola Arriga; Dario Papale; Paul C. Stoy; Nina Buchmann; Matthias Cuntz; John Douros; Silvano Fares; Alexander Knohl; Ladislav Šigut; Guillaume Simioni; et al. (Science of The Total Environment, 2023)

Bi‐directional soil/atmosphere N 2 O exchange over two mown grassland systems with contrasting management practices - CHRISTOPHE R. FLECHARD; ALBRECHT NEFTEL; MARKUS JOCHER; CHRISTOF AMMANN; JÜRG FUHRER (Global Change Biology, 2005)
Nitrous oxide (N 2 O) fluxes from soil under mown grassland were monitored using static chambers over three growing seasons in intensively and extensively managed systems in Central Switzerland. Emissions were largest following the application of mineral (NH 4 NO 3 ) fertilizer, but there were also substantial emissions following cattle slurry application, after grass cuts and during the thawing of frozen soil. Continuous flux sampling, using automatic chambers, showed marked diurnal patterns in N 2 O fluxes during emission peaks, with highest values in the afternoon. Net uptake fluxes of N 2 O and subambient N 2 O concentrations in soil open pore space were frequently measured on both fields. Flux integration over 2.5 years yields a cumulated emission of +4.7 kgN 2 O‐N ha −1 for the intensively managed field, equivalent to an average emission factor of 1.1%, and a small net sink activity of −0.4 kg N 2 O‐N ha −1 for the unfertilized system. The data suggest the existence of a consumption mechanism for N 2 O in dry, areated soil conditions, which cannot be explained by conventional anaerobic denitrification. The effect of fertilization on greenhouse gas budgets of grassland at the ecosystem level is discussed.